Multicultural Worship: Theory and Practice - Kim, Eunjoo Mary (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We live in an unprecedently globalized multicultural world in the 21st century. Christian churches and worship leaders are challenged to be conscious of the significant impact of multiculturalism within and beyond the church and provide worshipers with theologically faithful and culturally appropriate worship services. As a response to these challenges, this Special Issue deals with various multicultural issues emerging from contemporary liturgical contexts: What is multicultural worship? Why should Christian worship be multicultural? How can multicultural worship be designed to be relevant to a particular liturgical context? How can liturgical elements (e.g., worship space, symbols, language, sermons, prayers, music, and sacraments) be prepared from the multicultural perspective? This Special Issue provides worship leaders with theological and liturgical insights into exploring these questions and developing their theology and method of multicultural worship. In addition, sample liturgies and case studies with annotations offer concrete examples of multicultural worship. The scope of this Special Issue includes five areas: (1) multicultural worship in multiracial or multiethnic contexts; (2) multicultural worship in monoracial or monoethnic contexts; (3) multicultural worship in multigenerational contexts; (4) multicultural worship in ecumenical contexts; and (5) multicultural worship in multireligious contexts. While there are some resources available for studying multicultural worship, this volume uniquely contributes with diverse cultural approaches to various liturgical contexts.